Dose kidney transplant nephrectomy stop disease progression in plasma exchange resistant post transplant hemolytic uremic syndrome? A case report - Farzaneh Sharifipour; Abbasali Zeraati; Seyed Seifollah Beladi Mousavi; Fatemeh Hayati; Mohsen Tavazoe; Marzieh Beladi Mousavi (Society of Diabetic Nephropathy Prevention, 2013)
Background: Two different case reports, which have been published previously, suggested that bilateral nephrectomy can improve sever and refractory hemolytic uremic syndrome (HUS) in adults without a history of transplantation. At this study, kidney transplant nephrectomy in a patient with sever post transplant HUS was investigated. Case: Patient was a 55 years old man with a single small size kidney and end-stage renal disease (ESRD). He had received a kidney from an unrelated donor three months before admission. The patient was admitted with fever and acute renal failure. Clinical and laboratory evaluation wereconsistent with sever De novo hemolytic uremic syndrome (HUS). Different therapeutic regimens administered in this patient including intensive plasma exchange, plasma infusion, empirical antibiotics, and high doses of corticosteroid. Although Cyclosporine was changed to Tacrolimus. After 45 days of treatment, patient's condition did not improve and sever thrombocytopenia (10000-15000/µL) developed. Patient was also suffered from severe hypersensitivity reaction (fever, chills, and itching) following each plasma exchange. Kidney transplant nephrectomy was done. However, sever post operativebleedingoccurred.HUS and thrombocytopenia did not improve and patient died two days after operation. Conclusions: According to this experience, Kidney transplant nephrectomy may not be an effective treatment and is not recommended in the treatment of severe and refractory post transplant HUS.